Pragmatic Studies in At-Thabari's Interpretation of Q.S. Al-Ahzab: 33 - Windariyah, Devi Suci (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze At-Thabari's interpretation of the Qur'an surah Al-Ahzab verse 33. To reveal the deep meaning contained in At-Thabari's interpretation of Surah Al-Ahzab verse 33, researchers use a pragmatic approach to examine the meaning contained in analyzing At-Thabari's interpretation in interpreting Surah Al-Ahzab verse 33. The research method used is a descriptive qualitative research method with Content Analysis to analyze messages in different situations, the difference in these situations is in the form of different contexts. The data validity technique used is source triangulation. The results of research from this study are important messages implied by the derivation of the Qur'an Surat Al-Ahzab verse 33, is There are two messages implied from the interpretation of At-Thabari to the Qur'an Surat Al-Ahzab verse 33, namely First, how is the role of a father as the head of the family as exemplified by the Prophet Muhammad SAW, Second, how to purify yourself, mind and heart.